Mechanistic Insights into Cyclic Voltammograms on Pt(111): Kinetics Simulations. Issue 21 (2nd October 2019) - Shen, Dongyan; Liu, Yong; Yang, Guangxing; Yu, Hao; Peng, Feng
Abstract: A detailed understanding of the electrochemistry of platinum electrodes is of great importance for the electrochemical oxidation of fuels and electrochemical reduction of dioxygen in fuel cells. The Pt(111) facet is the most representative model mimicking Pt nanoparticles and polycrystals for fundamental studies. Herein, we propose a site‐specific model accompanied with the typical elementary steps of the electrochemistry of Pt(111) in non‐adsorbing electrolyte within the potential range between 0.05 and 1.15 V versus reversible hydrogen electrode. Simulations were conducted at different scanning rates based on the kinetics models. We reproduce all the anodic and cathodic peaks observed in the reported experimental curves. These results demonstrate the underlying mechanisms of the peak formation in different potential regions. Abstract : Model electrochemistry : A site‐specific model accompanied by the typical elementary steps of electrochemistry on Pt(111) in non‐adsorbing electrolyte is proposed. The cyclic voltammograms within the potential range between 0.05 and 1.15 V (vs. RHE) are exactly reproduced at different scan rates from 0.005 V to 5 V s −1, providing mechanistic insights into the electrochemistry of Pt nanoparticle and polycrystal in fuel cell systems.